The Relationship Between Knee Pain and Quality of Life in the Elderly - Prawidiyanti, Abi Muji; Aswar, Andini (Jurnal Ar Ro'is Mandalika (Armada), 2026)
The quality life of elderly people would be better of, if they have independency, good physical health and if they stay active doing daily activity. One of the cause in decrease health quality on elderly people is disability.Where the most cause of disability in some cases turn out to be joint pain with prevalence of 54,8. Joint pain cause a decreased quality of life on elderly people because of the hardtime and the limitation in doing activity. Goals: evaluate prevalence of knee pain in elderly at Panti Sosial Tresna Werdha Budi Mulia 2, evaluate risk factor of pain in elderly. Sample consist of 123 people and collected using consecutive non random sampling. Respondent data was acquired by interview and questionnaire. The data was analyzed using SPSS program and Chi-square test. The study show that most of the elderly suffered from knee pain which consist of 91 people (74%). It also show that theres a meaningful association between body mass index with knee pain (p=0,001), while age, gender, educational level, smoking habit, do not have an association with knee pain. This study show theres a meaningful association between knee pain with quality of life knee pain could affect the quality of life on elderly.